Utility of diagnostic tests in vomiting dogs presented to an internal medicine emergency service - Holzmann, Bettina; Werner, Melanie; Unterer, Stefan; Dörfelt, René (Frontiers in Veterinary Science, 2023)
Vomiting is a common sign in dogs presenting to emergency services. It can be self-limiting, a sign of a life-threatening extraintestinal, or intestinal disorder. Reasonable diagnostics should be performed to determine the underlying cause. This study aimed to assess the utility of diagnostic tests in vomiting dogs, and its correlation with patient history, and physical examination results. Additionally, parameters to differentiate uncomplicated vomiting from complicated vomiting were investigated. In this prospective, observational, clinical study, data from 99 client-owned dogs with vomiting, presenting as first opinion cases, were evaluated. History, physical examination, duration of clinical signs, overall number of episodes of vomiting, appetite, and additional clinical signs were recorded. The standardized diagnostic evaluation of all patients included venous blood gas analysis, complete blood count, serum biochemistry profile, canine pancreatic lipase, abdominal radiographs, ultrasound, and urinalysis. Follow-up was performed 4–5 days later. Based on severity of disease and clinical course, dogs were categorized to “uncomplicated vomiting” (UN), or “complicated vomiting” (COM). The utility of each test for diagnosing the cause of vomiting was evaluated. Spearman correlation coefficient, Chi-squared-, unpaired t-, and Mann–Whitney U-test were used. Statistical significance was defined as p ≤ 0.05. Out of the 99 dogs, 34 had uncomplicated courses of disease (UN). In 60/99 cases, a diagnosis was obtained, and in 39/99 cases, the cause for vomiting remained unknown. Longer duration of clinical signs, and reduced appetite were associated with higher utility of abdominal ultrasound. A poor mentation was associated with a higher utility of blood examinations and abdominal radiographs. Dogs presenting with an impaired mentation or with additional clinical signs other than diarrhea, were more likely to be in the COM group. Based on this investigation, general recommendations concerning the diagnostic approach for patients with vomiting could not be provided. For dogs who have exclusively vomiting as a clinical sign, and present in good mentation, further investigations might not be beneficial, and these dogs may recover with symptomatic treatment alone. Additional diagnostics could be indicated in dogs with additional clinical signs other than diarrhea.